ECHO CHAMBER DAN FENOMENA TERBENTUKNYA KOMUNIKASI HOMOGEN - Cevi Mochamad Taufik (UKRI, 2026)
Beliefs in truth are acquired solely from a single viewpoint without referring to numerous other sources and references widely available across online channels. Digitalization, along with its derivative product social media, opens up echo chambers that validate truth messages, ultimately shaping shared beliefs. These beliefs form because algorithms play a crucial role by transforming diverse opinions into uniform ones. The phenomenon of fake truths, which ignores other perspectives with more valid and accountable truth values, finds no place. Communication becomes homogenized by negating all possibilities from diverse perspectives. Based on this background, this research aims to analyze the echo chamber phenomenon that leads to highly homogenized communication in digital spaces. The method used is qualitative with a virtual ethnography approach to analyze phenomena occurring in digital spaces as a result of internet users' habits trapped in algorithms. The research findings indicate that echo chambers occur due to content traps that encourage social media users to follow specific accounts, where information entering the home feed follows the algorithmic system deemed similar and meeting the preferences of the account user, causing communication to become homogenized.